Pengaruh Sistem Informasi Akuntansi, Literasi Keuangan, Manajemen Kas dan Modal Terhadap Kinerja Keuangan Pada Mitra UMKM Alfamart Kebayoran Lama - Dendyansyah, Dendyansyah (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the role of financial management in improving the financial performance of Alfamart's MSME partners by researching the use of accounting information systems, financial literacy levels, cash management practices, and business capital. This study uses a descriptive quantitative approach by distributing questionnaires to 60 MSME actors who are Alfamart partners in Kebayoran Lama, selected using accidental sampling techniques. The data analysis used included multiple linear analysis and hypothesis testing. The results indicate that although MSMEs obtain market access support through partnership programs, there are still limitations in cash flow management and financial recording that can affect business consistency. Cash management was found to have an effect on financial performance, with a tangible contribution to facilitating operational activities and controlling cash flow. Meanwhile, accounting information systems, financial literacy, and capital did not show a significant effect on the financial performance of Alfamart Kebayoran Lama MSME partners